Automatic generation of structured multiblock boundary layer mesh for aircrafts. (January 2018) - Lu, Fengshun; Pang, Yufei; Jiang, Xiong; Sun, Junfeng; Huang, Yong; Wang, Ziwei; Ju, Jiali
Highlights: Structured meshes are widely utilized in aircraft industry because of their computational efficiency and accuracy for viscous flows of complex configurations. However, the mesh generation process usually involves tremendous interactions between professional engineers and commercial software. To address this issue, we endeavor to investigate the automatic structured mesh generation techniques for arbitrary aircrafts and present part of our achievements here. Our contributions are as follows. A novel data structure that describing the mesh entities and eliminating the many-to-many relationship between them. Structured meshes can be represented with four physical entities, namely endpoint, connector, domain and block . However, there are many-to-many relationships between the four physical entities. For instance, an endpoint can be shared by many connector s and each connector owns two endpoint s. The complex relationships put great obstacles for the manipulation of mesh objects: when adding or deleting a physical entity, you must carefully deal with the relevant many-to-many relationship. We introduce five logical entities ( capstone, range, edge, region and face ) to eliminate the many-to-many relationship and make the data structure become a six-node chain. Note that the chain starting from capstone to range and then to block only has the one-to-one relationship. A method that can automatically generate structured multiblock boundary layer mesh with surface mesh as its input. The automatic generation process includes three steps. First, the geometry features needed to construct the mesh frame are extracted from the surface mesh. For each endpoint shared by four domain s in the discrete surface mesh, we generate a supporting line with the directional vector calculated by our proposed algorithm. Second, the mesh frame for the boundary layer mesh is constructed based on the extracted geometry features. A mesh frame consists of many connector s, which behave as the skeleton of the mesh. Third, the interior grid points of the boundary layer mesh are generated with the Transfinite Interpolation method. A detailed verification of the proposed method with three cases by several well-acknowledged mesh quality metrics. The utilized examination functions are Jacobian information, included angles andaspect ratios. We select three cases to verify our proposed method. The first case corresponds to several challenging scenarios (convex and concave steps) confronted in generating boundary layer meshes for various aircrafts, and the last two cases present the diagnostic information about practical aircrafts, namely a four-rudder missile and the F6 wing-body half model. Experimental results show that all the grid cells are positive, which satisfies the fundamental requirement about the mesh for the CFD solvers. Abstract: Structured meshes are widely utilized in the aircraft industry, despite their requirement for significant interaction between the engineers and the commercial software used in the generation process. In this research, we introduce part of our achievements while investigating the automatic generation techniques for structured meshes of arbitrary aircrafts. First, we present a data structure that eliminates the many-to-many relationship between various physical entities representing the discrete mesh. Second, we propose a novel method that can automatically generate a structured multiblock boundary layer mesh using an input surface mesh. Finally, we verify the proposed method with three cases (i.e., convex/concave steps, a four-rudder missile and the F6 wing-body half model) by the metrics Jacobian, included angles and aspect ratios. These experiments show that our proposed method can automatically generate structured multiblock boundary layer mesh for aircrafts.